Immunological images of polycyclic aromatic hydrocarbons - Glushkov, A.N.; Kostyanko, M.V.; Anosova, T.P.; Polenok, E.G.; Mun, S.A.; Anosov, M.P.; Cherno, S.V. (Experimental Oncology, 2006)
Aim: To develop experimental model for definition of immunological images of chemical carcinogens. Materials and Methods: The conjugates of benzo[a]pyrene, benz[a]anthracene, anthracene, chrysene and pyrene with bovine serum albumin and yeast hexokinase were synthesized. Rabbits were immunized by bovine serum albumin-hapten conjugates. Antibodies to each hapten were isolated from the serum by affinity chromatography with the hapten-yeast hexokinase-Sepharose sorbents. The binding of each hapten with each antibody was determined by competitive immunoassay. Results: The immunological images of all the investigated chemical compounds were described. Conclusion: The model is proposed to determine the internal immunological images of anti-idiotypic monoclonal antibodies to chemical carcinogens. Цель: разработка экспериментальной модели для определения иммунологических образов химических канцерогенов. Материалы и методы: синтезированы конъюгаты бензо[a]пирена, бенз[a]антрацена, антрацена, пирена и хризена с бычьим сывороточным альбумином и дрожжевой гексокиназой. Кроликов иммунизировали конъюгатами с бычьим сывороточным альбумином в качестве белка-носителя. Антитела к каждому из гаптенов выделяли из сыворотки аффинной хроматографией на сорбентах гаптен-дрожжевая гексокиназа-Sepharose. Способность антител связываться с соответствующими гаптенами определяли с помощью конкурентного иммуноанализа. Результаты: в результате исследования охарактеризованы иммунологические образы исследуемых химических канцерогенов. Выводы: предложенная модель дает возможность определять внутренние иммунологические образы антиидиотипических моноклональных антител к химическим канцерогенам.